Zeeman en Einstein. Meeslepende metingen - Maas, Ad; Pimentel, Beto (Studium, 2016)
Zeeman and EinsteinThis article discusses an early example of interferometric, experimental research related to Einstein’s Special Theory of Relativity. This research concerned two series of experiments on the velocity of light in moving media, conducted between 1914 and 1921 by the Amsterdam physicist Pieter Zeeman. With the first of these series, on the velocity of light in moving water, Zeeman obtained an important result that validated the so called ‘dispersion term’ of the formula for the velocity of light in moving media. Less clear is the scientific objective of the second series, in which Zeeman measured the velocity of light in moving solid media. It seems that Zeeman’s interest in this second series was triggered mainly by the technical challenges posed by these experiments. In this way, they reveal the increasing tendency of Zeeman’s later research to be led by technical and experimental challenges, rather than by the actual scientific developments.